Biochar production techniques utilizing biomass waste-derived materials and environmental applications – A review - Farah, Amalina; Abdul Syukor, Abd Razak; Santhana, Krishnan; Haspina, Sulaiman; A. W., Zularisam; Mohd, Nasrullah (Elsevier Ltd, 2022)
Biochar is an incredibly rich source of carbon formed through biomass's thermal decomposition. There is a rise of interest in employing biochar derived from biomass in various disciplines to address the most significant environmental challenges. This article evaluated and presented the preparation, characterization, and, most importantly, the environmental application of biochar in a comprehensive way. Process parameters are primarily responsible for determining biomass production. The physicochemical properties of biochar vary according to the type of biomass used. The development of biochar utilizing a variety of different approaches has been discussed. Biochar is typically prepared through pyrolysis, gasification, or hydrothermal carbonization. Biochar has been used in various applications, including soil remediation and enhancement, carbon sequestration, organic solid waste composting, water and wastewater decontamination, catalyst and activator, electrode materials, and electrode modifier. In summary, biochar has a vast number of possible uses in environmental reduction and the mechanism by which its performances should be further investigated.